Manufacturing strategy in small firms: unveiling the drivers of strategic consensus. Issue 1 (2nd January 2022) - Veloso Saes, Elizangela; Godinho Filho, Moacir; Thürer, Matthias; Chiappetta Jabbour, Charbel Jose; Lopes de Sousa Jabbour, Ana Beatriz; Carraro, Nilton Cezar; Oprime, Pedro Carlos
Abstract: Strategic consensus can be defined as agreement on strategy content and process across all levels of an organisation. Although strategic consensus is considered a major factor for the success of any manufacturing strategy, the topic has been widely neglected in the operations management literature. Moreover, the limited existing literature typically focusses on large firms in developed economies. In response, this study explores strategic consensus in 38 small companies in Brazil. Multiple company visits were combined with surveys and interviews. Responses from all operational managers (55 responses) and 117 operational-level employees (operators) were obtained. Using cluster analysis this study tests 10 research propositions regarding drivers of strategic consensus that where obtained through a systematic literature review. Results suggest that a high degree of formalisation in planning activities supports strategic consensus, that professional and decentralised decision making may be a better alternative for small firms and that the formalisation of communication channels may not be mandatory for strategic consensus, if there is, for example, a close relationship and collaboration between managers and employees.